PELAKSANAAN PEKERJAAN STRUKTUR BAWAH BANGUNAN GEDUNG SERBAGUNA GELANGGANG GENERASI MUDA MAJALENGKA - Gumilar, Raharja; Hendrayana, Yayat (Universitas Majalengka, 2024)
The Majalengka Regency Youth Center Development Project is an important historical milestone for infrastructure development in the Majalengka Regency area. The concept of an oval-shaped building like a stadium gives uniqueness to the design of the foundation of this building. Basically, the substructure is a very vital component for the success of a building, so the author is interested in looking further into the substructure, especially in work methods or work implementation. This research uses a qualitative approach, which can be interpreted as directly describing the work of the lower structures in the project which is used as the research object. The implementation of the lower structure work starts with the piling work and then continues with the pile cap work, carried out in stages using a zone system. In the realization of the implementation of the lower structure work on the GGM project, namely the piling work starting from site preparation, mobilization and set up of HSPD piling tools, measuring pile points, driving piles using the hydraulic jack-in pile method, testing piles, and pile head treatment, continued with the implementation of pile cap work starting from preparation, measurement and bow plank, soil excavation, installation of formwork, reinforcement and casting.